FRET and FRAP imaging: Approaches to characterise tau and stathmin interactions with microtubules in cells. (15th February 2013) - Nouar, Roqiya; Devred, François; Breuzard, Gilles; Peyrot, Vincent
Abstract: Microtubules (MTs) are involved in many crucial processes such as cell morphogenesis, mitosis and motility. These dynamic structures resulting from the complex assembly of tubulin are tightly regulated by stabilising MT‐associated proteins (MAPs) such as tau and destabilising proteins, notably stathmin. Because of their key role, these MAPs and their interactions have been extensively studied using biochemical and biophysical approaches, particularly in vitro . Nevertheless, numerous questions remain unanswered and the mechanisms of interaction between MT and these proteins are still unclear in cells. Techniques coupling cell imaging and fluorescence methods, such as Förster resonance energy transfer and fluorescence recovery after photobleaching, are excellent tools to study these interactions in situ . After describing these methods, we will present emblematic data from the literature and unpublished experimental results from our laboratory concerning the interactions between MTs, tau and stathmin in cells. Abstract : The dynamic behaviour of microtubules (MTs) is finely regulated by interactions with MT‐associated proteins. These interactions have been extensively studied in vitro by biochemical and structural approaches, but remain difficult to investigate in a cellular context mainly due to poorly adapted methods. Advanced fluorescence techniques such as Förster resonance energy transfer and fluorescence recovery after photobleaching are appropriated techniques to characterise the interactions between MTs and their associated proteins such as tau or stathmin directly in cells.